Assessing curve number uncertainty for green roofs in a stochastic environment - Huang, W S C; You, L W; Tung, Y K; Yoo, C S (IOP conference series. Earth and environmental science, 2018)
Curve number (CN) is well-known by hydrologists for estimating rainfall induced runoff from a catchment. It can also be used as an indicator for measuring the impact of engineering or non-engineering measures on the runoff production in a catchment. In this study, a method is presented to quantify the uncertainty of CN for hydrologic performance of a green roof system. Latin hypercube sampling approach, coupled with the antithetic variate technique, is used to achieve efficient and accurate quantification of the uncertainty features of CN for a green roof system. Elements in green roofs subject to uncertainty considered are rainfall characteristics (i.e. amount and inter-event dry period), soil-plant-climate factors (i.e. field capacity, wilting point, interception, evapotranspiration rate), and model error in SCS Ia-S relation. Numerical study shows that model error in SCS Ia-S relation has the dominant effect on the uncertainty features of CN for green roof performance.